Design of Expert System Application for Android-Based DSLR Camera Damage Diagnosis - Wulandari, Ria; Jonas, Dendy; Alwarits, Naufal Fadhil (Pandawan Sejahtera Indonesia, 2020)
In the digital age it is possible for everyone to do anything including documenting moments. One of them is digital camera based on Digital Single Lens Reflex or DSLR. But sometimes the use that is not according to the procedure can cause damage to the camera. As a layman, of course, will be confused with the problems that arise when there is damage and will be more decided to buy a new one or sell it, even though the damaged camera can still be repaired alone or by expert technicians. To solve the problem, an Expert System was created to diagnose damage to the Digital Single Lens Reflex camera. The method used in this research is the method of needs analysis and data collection. The results of this expert system application can diagnose damage to the Digital Single Lens Reflex camera along with alternative solutions. This application can help people to be more sensitive to the condition of their Digital Single Lens Reflex cameras. The design of this application was created with the help of joomla and sublime text.